For a tika transition: strengthen rangatiratanga - Bargh, Maria; Tapsell, Ellen (Policy Quarterly, 2021)
Examines two prominent environmental issues – sea level rise and taonga species protection – facing iwi, hapū, Māori and the Crown, exploring the barriers, solutions and positive steps in each area towards a ‘tika transition’ whereby iwi, hapū and Māori (the rangatiratanga sphere) and the Crown (kāwanatanga sphere) exist within distinct and equal political entities, with the rangatiratanga sphere leading and governing tikanga and mātauranga Māori policy and legislation. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: citizenship; climate change; co-governance; environment; environmental management; government relations; kāwanatanga; mātauranga māori; protection; rangatiratanga; sea level; taonga; tikanga | indigenous law

Fostering sustainable tribal economies in a time of climate change - Bargh, Maria; Douglas, Sarsha-Leigh; Te One, Annie (New Zealand geographer, 2014)
In this article, we explore how Māori tribal organisations are responding to calls by other Indigenous peoples to become more sustainable in a time of climate change. From a close examination of tribal Environmental Management Plans, we move to a specific case study in the Bay of Plenty area, Ngāti Kea/Ngāti Tuara. Ultimately, we suggest that many tribal organisations are seeking to respond to climate change and transition to becoming producers of their own food and energy needs, and are often articulating these responses in relation to specific local resources and contexts.
Keywords: climate change; economic aspects; environmental management; iwi; iwi development; sustainable development